(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Webseries have emerged as a popular form of entertainment in recent years. Webseries are generally fictitious or non-fictional long-form narrative telling in episodic forms that are displayed on various online streaming platforms. In the present competitive environment, E-commerce sites, cellular network vendors, and film studios, are producing and disseminating Webseries. Novels give ready-made storylines for Webseries creators to take their creative work to the next level and help disseminate it to an audience who is not into the habit of reading literature. Webseries based on novels are continually emerging and capturing the audience’s attention while keeping them waiting for a sequel.People who are not accustomed to reading might connect with it through various stories derived from novels and exhibited in Webseries.